Three‐Dimensional Transesophageal Echocardiography Assessment of a Successful Transcatheter Mitral Valve in Valve Implantation for Degenerated Bioprosthesis. Issue 6 (12th March 2013) - Théron, Alexis; Gariboldi, Vlad; Grisoli, Dominique; Maysou, Laurie‐anne; Jaussaud, Nicolas; Morera, Pierre; Cuisset, Thomas; Quilici, Jacques; Thuny, Franck; Riberi, Alberto; Avierinos, Jean‐François; Collart, Frederic
Abstract : Reoperation for degenerated mitral bioprosthesis is considered a high risk procedure. Transcatheter mitral valve in valve implantation has emerged as an off‐label alternative for patients contra‐indicated to surgery. We report a 46‐year‐old man, with a 29 mm mitral bioprosthesis since 2002, who was admitted for acute heart failure because of a severe intra‐prosthetic regurgitation. His recent medical history revealed a fast growing cavum carcinoma. In view of generally poor prognosis, the heart team decided to perform a transcatheter mitral valve in valve implantation by transapical approach. Live three‐dimensional TEE was used during the implantation for sizing, device positioning, and hemodynamic assessment. Mini‐Abstract: Reoperation for degenerated mitral bioprosthesis is considered a high risk procedure. Transcatheter mitral valve in valve implantation has emerged as an off label alternative for patients contra‐indicated to surgery. During the implantation, live three‐dimensional (3D) TEE is an accurate imaging modality for sizing, device positioning, and hemodynamic assessment.